POTENTIAL OF RED OKRA (Abelmoschus esculentus (L.) Moench) ETHANOL EXTRACT TO PROTECT AGAINST 7, 12-DIMETHYLBENZ[A]ANTHRACENE-INDUCED DAMAGE IN RAT'S (Rattus norvegicus) Liver - Lukiteswari Dyah Tri Hapsari; Kusuma Eko Purwantari; Indri Safitri Mukono; Sri Puji Astuti Wahyuningsih; Nadyatul Ilma Indah Savira (Universitas Airlangga, Surabaya, Indonesia, 2024)
Highlights: Red okra pods have a potential antioxidant to protect against DMBA-induced damage in a rat's liver. The liver protection with ROE decreased reversible and irreversible cellular damage from 51.8% to 35%, 27.3%, and 18.9%. Abstract Background: Okra (Abelmonchus esculentus (L.) Moench) is a plant that has potential for humans and health because it contains high antioxidants such as polyphenols. Objective: This study aimed to analyze the red okra pods' ethanol extract (ROE) antioxidant potential to protect rat (Rattus norvegicus L.) liver against damage by induction of 7, 12-dimethyl-benz[a]anthracene (DMBA). Material and Method: The material used was various doses of red okra pods with ethanol as solvent. Twenty-five female rats (4 weeks, body weight 140”150 g) were divided into five groups: negative control (receiving a single dose of 0.5 mL corn oil as DMBA solvent), positive control (receiving a single dose induction of DMBA 80 mg/kg BW dissolved in 0.5 mL corn oil), and treatment groups 1, 2, 3 (receiving a single dose of DMBA 80 mg/kg BW dissolved in 0.5 mL corn oil and ROE of 50, 100, and 200 mg/kg BW, respectively, daily for 35 days). On day 36, the livers were removed and prepared for histopathological observation using hematoxylin-eosin staining. The method of histopathological score was determined using an ordinal score. Result: The data were analyzed statistically (p>0.05). All ROE doses showed a significant decrease in the histopathological score of rats' liver damage caused by DMBA-induced. The liver protection with ROE reduced the percentages of reversible and irreversible cellular damage from 51.8% to 35%, 27.3%, and 18.9%, respectively. Conclusion: The red okra pod ethanol extract can protect against DMBA-induced liver damage in rats.